Theodore and the Talking Mushroom - Lionni, Leo 1910-1999. (New York : Knopf, 2009)
Theodore, a timid mouse who is constantly being ridiculed by his friends, runs into trouble when he discovers a huge blue mushroom and pretends that it can talk.
"A Borzoi book."
Keywords: Mushrooms -- Fiction; Mice -- Fiction; Honesty -- Fiction; Self-esteem -- Fiction